THEORATICAL FRAMEWORK TO UNDERSTAND THE ASSOCIATION OF ORGANIZATIONAL CHANGE ON THE ORGANIZATIONAL COMMITMENT (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The organization change is defined as the adoption of new ideas or behavior by an organization. The mainobjective of organizational change is to maximize the benefits of the people involved in the process and to minimize the risk involved in the failure of implementing and managing change. Organization commitment of the employees is an intangible asset for an organization so as to derive strategic advantage over competitors. It is a psychological link between the employee and his organization. If the employees lack commitment it willlead to increase in absenteeism and affecting labor turnover. The commitment employees will hence ease stressduring organizational change process and will understand and cope with change so as to make it successful. The paper helps to understand the organizational change initiatives undertaken in the organizations. It further helpsto examine the relationship between change management and organization commitment in organizations.Keywords: Organizational change, Change levers, Organizational change initiatives, organization commitment